Simulation of durability the evaluation of relief-dot Braille images - Havenko, Svitlana; Havenko, Mykola; Labetska, Marta (Journal of Graphic Engineering and Design, 2016)
The paper presents a model of factors that influence on the quality of relief-dot Braille inscriptions in their intensive use by blind people. It was constructed matrix of depending and distancing by using a directed graph. It allowed establish a hierarchy between studied criteria’s of impact the on durability of relief prints. It was developed a basic structure of digital system of assessment the conformity of Braille symbols to applicable international standards and definition of operational stability.